Design and application of the digital multifunctional ionosonde. Issue 7 (1st August 2016) - Gong, Wanlin; Cui, Xiao; Pan, Lingyun
Abstract : A multifunctional ionosonde was designed for ionospheric scientific research and monitoring applications by the Ionospheric Laboratory of Wuhan University during 2012–2014. This ionosonde is a high‐frequency (HF) radar using inter‐pulse phase codes and linear frequency modulation with high sensitivity. The two basic sounding modes of the radio system are the fixed frequency mode and the swept frequency mode. Both the radar waveform and the sounding mode are optional, based on practical considerations. This ionosonde can be applied to study the space environment, for applications such as to observe the disturbance and irregularities in the ionospheric E‐ and F‐layers, to record the propagation features of the HF radio waves, to detect the state of the ocean and so on. With different transmitting antennae, the same ionosonde can operate as a vertical‐incidence ionosonde, an oblique‐incidence ionosonde or an oblique‐backscatter ionosonde. Specifically, the ionosonde could be used to detect the state of the ocean by combining the sky wave with the ground wave. In this study, the architecture of the multifunctional ionosonde is introduced, and some initial observations of this ionosonde are presented.